Estresse e Burnout em trabalhadores da indústria petrolífera - Almeida, Brenda do Amaral (2017)
The inherent peculiarities of environment working industry, the demand for greater productivity, the tasks complexity and the time limitation can enhance the possibilities of accidents and health problems, among them Stress and the Burnout Syndrome. Thus, it’s important that the nurse, as a health team member, understanding the health-disease relationship in the oil industry work environment, aiming to generate subsidies for the nursing intervention in the stress of these workers, a better living condition to the worker and quality at work. Objective: To determine the intensity of stress, burnout and the stressors of oil industry workers. Methodology: A cross-sectional, exploratory, descriptive, field study with a quantitative approach was performed among 89 workers from a municipality oil industry of Rio de Janeiro, Brazil. The data were collected using self-applied instruments: Sociodemographic and work variables; Work Stress Scale and Maslach Burnout Inventory. Results: The participants were male (79.8%); in the age group up to 30 years (49.4%) with monthly income from 2 to 4 minimum wages (43.8%); of the operational (52.8%) and administrative (47.2) sectors; with "up to 2 years" of time in the function (44.9%). The stress intensity was moderate/high (74.2%), correlated with income (p-value 0.005) and time in function (p-value 0.018). The burnout emotional exhaustion intensity was high (52.8%), correlated with age (p-value 0.033), administrative sector (p-value 0.004) and time on function (p-value 0.041). The stressors were categorized in: "Working conditions" (52.77%); "Interpersonal relations" (44.44%) and "Professional recognition" (2.77%). Product: Educational technology, at a booklet form about stress and burnout in the oil industry worker health, aimed at instructiving occupational health nurses about stress and burnout. Conclusion: The oil industry workers have high level of stress at work and stress chronicity is evidenced by the workers emotional exhaustion burnout. The results corroborate with findings from other studies that indicate the importance of stress identification and stressors, data of great relevance for the implementation of health actions by the occupational health nurse, aiming at the planning of interventions for prevention of aggravations, health promotion and the worker wellness.